2012
DOI: 10.1080/10502556.2012.682896
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Divorce Cases in the United Arab Emirates: A Rising Trend

Abstract: The United Arab Emirates (UAE), located in the Arabian Gulf, has undergone significant social changes over the last 50 years. In addition to the positive social changes that have occurred since the discovery of oil, there also has been an increase in social problems, including divorce. Divorce rates are on the rise in the UAE, and the government is particularly concerned with the rising divorce rate among its citizens. Using both document analysis and in-depth interviews, this study sought to explore reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
4
19
0
Order By: Relevance
“…Thus, pertinent questions as basic as what constitutes marital satisfaction in the Gulf Arab culture, to complex ones such as what social, cultural, and psychological factors may be associated with marital satisfaction in Gulf Arab societies, remain mostly unaddressed. Considering the increasingly higher divorce rates in Downloaded by [Nanyang Technological University] at 01:25 06 June 2016 the UAE society (Al Awadhi, 2007;Al Gharaibeh & Bromfield, 2012;Emirates 24/7 News, 2011;Safdar, 2009) and the region (Alqashan, 2008), this deficiency of literature seems to be quite worrisome and this sets the significance and urgent relevance of this study. According to the National Bureau of Statistics, UAE, the period 2011-2013 recorded a total of 12,279 divorces.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, pertinent questions as basic as what constitutes marital satisfaction in the Gulf Arab culture, to complex ones such as what social, cultural, and psychological factors may be associated with marital satisfaction in Gulf Arab societies, remain mostly unaddressed. Considering the increasingly higher divorce rates in Downloaded by [Nanyang Technological University] at 01:25 06 June 2016 the UAE society (Al Awadhi, 2007;Al Gharaibeh & Bromfield, 2012;Emirates 24/7 News, 2011;Safdar, 2009) and the region (Alqashan, 2008), this deficiency of literature seems to be quite worrisome and this sets the significance and urgent relevance of this study. According to the National Bureau of Statistics, UAE, the period 2011-2013 recorded a total of 12,279 divorces.…”
Section: Introductionmentioning
confidence: 90%
“…A. Johnson et al, 2001). International studies have found highly endorsed reasons for divorce to be marrying too young, communication problems, incompatibility, spousal abuse, drug and alcohol use, religious differences, failures to get along, lack of love, lack of commitment, and childlessness, to name a few (Al Gharaibeh & Bromfield, 2012; Savaya & Cohen, 2003a, 2003b; Mbosowo, 1994). …”
mentioning
confidence: 99%
“…Marriage and divorce have been among the most significant topics that have been recently investigated in the UAE by several researchers (e.g. Al Gharaibeh and Bromfield, 2012;Bromfield, 2014; Al Gharaibeh, 2015; Bromfield et al 2016 among others). The rising divorce rate is detrimental to families, especially children (see Al Gharaibeh, 2015: 357).…”
Section: Introductionmentioning
confidence: 99%